Can common strengths be identified in autistic young people? A systematic review and meta-analysis. (October 2022) - Devenish, B.D.; Mantilla, A.; Bowe, S.J.; Grundy, E.A.C.; Rinehart, N.J.
Abstract: Background and method: The purpose of this study was to systematically review the empirical literature on common strengths of autistic young people relative to their typically developing peers. Results: Forty-eight articles met inclusion criteria and were included. Of these, sixteen studies reported sufficient data for inclusion in a series of 13 meta-analyses. Only a small number of mean effect sizes were significant, with possible common strengths including auditory processing strengths (Hedges' g = 0.54–1.22) and metaphor generation (Hedges' g = 0.64). Conclusions: This review highlights the need for a systematic approach to identifying strengths shared by autistic young people that could inform intervention approaches, and are important to autistic young people and their families. Highlights: There is an absence of high-quality research that identifies common strengths in autistic young people. Strengths of autistic young people may include intuitive physics, and strengths related to being less bound by conventions. Future research exploring potential strengths can help recognise and celebrate the neurodiversity of autistic young people.